Antecedents Of Intrinsic Motivation, Metacognition And Their Effects On Students' Academic Performance In Fundamental Knowledge For Matriculation Courses - Mikail Ibrahim; Normah Othman; Hazleena Baharun; Haliza Harun (Universiti Utara Malaysia Press, 2024)
Indexed by SCOPUS